Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

High-resolution free-breathing automated quantitative myocardial perfusion by cardiovascular magnetic resonance for the detection of functionally significant coronary artery disease - Crawley, R.; Kunze, K. P.; Milidonis, X.; Highton, J.; McElroy, S.; Frey, S. M.; Höfler, Daniel; Karamanli, C.; Wong, N. C.K.; Backhaus, S. J.; Alskaf, E.; Neji, R.; et al. (European Heart Journal - Cardiovascular Imaging, 2024)
Aims Current assessment of myocardial ischaemia from stress perfusion cardiovascular magnetic resonance (SP-CMR) largely relies on visual interpretation. This study investigated the use of high-resolution free-breathing SP-CMR with automated quantitative mapping in the diagnosis of coronary artery disease (CAD). Diagnostic performance was evaluated against invasive coronary angiography (ICA) with fractional flow reserve (FFR) measurement. Methods Seven hundred and three patients were recruited for SP-CMR using the research sequence at 3 Tesla. Of those receiving and results ICA within 6 months, 80 patients had either FFR measurement or identification of a chronic total occlusion (CTO) with inducible perfusion defects seen on SP-CMR. Myocardial blood flow (MBF) maps were automatically generated in-line on the scanner following image acquisition at hyperaemic stress and rest, allowing myocardial perfusion reserve (MPR) calculation. Seventy-five coronary vessels assessed by FFR and 28 vessels with CTO were evaluated at both segmental and coronary territory level. Coronary territory stress MBF and MPR were reduced in FFR-positive (≤0.80) regions [median stress MBF: 1.74 (0.90–2.17) mL/min/g; MPR: 1.67 (1.10–1.89)] compared with FFR-negative regions [stress MBF: 2.50 (2.15–2.95) mL/min/g; MPR 2.35 (2.06–2.54) P < 0.001 for both]. Stress MBF ≤ 1.94 mL/min/g and MPR ≤ 1.97 accurately detected FFR-positive CAD on a per-vessel basis (area under the curve: 0.85 and 0.96, respectively; P < 0.001 for both). Conclusion A novel scanner-integrated high-resolution free-breathing SP-CMR sequence with automated in-line perfusion mapping is presented which accurately detects functionally significant CAD.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cardiovascular magnetic resonance; CMR; coronary artery disease; myocardial blood flow; myocardial perfusion; quantitative perfusion

Long-term Results of oligometastatic Head and Neck Tumors after local Treatment of all Metastases - Weissmann, T.; Höfler, Daniel; Semrau, S.; Lettmaier, S.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

Outcomes of I-125 Low-Dose-Rate Brachytherapy in Patients with Localized Prostate Cancer: A Comprehensive Analysis from a Specialized Tertiary Referral Center - Schubert, Philipp; Strnad, Vratislav; Höfler, Daniel; Schweizer, Claudia; Putz, Florian; Lotter, Michael; Kreppner, Stephan; Karius, Andre; Fietkau, Rainer; Merten, Ricarda (Journal of Personalized Medicine, 2024)
Low-dose-rate (LDR) brachytherapy with I-125 seeds is one of the most common primary tumor treatments for low-risk and low-intermediate-risk prostate cancer. This report aimed to present an analysis of single-institution long-term results. We analyzed the treatment outcomes of 119 patients with low- and intermediate-risk prostate cancer treated with LDR brachytherapy at our institution between 2014 and 2020. The analysis focused on biochemical recurrence rates (BRFS), overall survival (OS), cumulative local recurrence rate (CLRR), and the incidence of acute and late toxicities. Patient-reported quality of life measures were also evaluated to provide a holistic view on the treatment’s impact. The median follow-up period was 46 months. CLRR was 3.3% (4/119), five-year BRFS was 87%, and the five-year OS rate was 95%. Dysuria was the most common acute urinary toxicity, reported in 26.0% of patients as grade 1 and 13.4% as grade 2. As a late side effect, 12.6% of patients experienced mild dysuria. Sexual dysfunction persisted in 6.7% of patients as grade 1, 7.5% as grade 2, and 10.0% as grade 3. LDR brachytherapy in patients with prostate cancer is an effective treatment, with favorable clinical outcomes and manageable toxicity. The low CLRR and high OS rates, as well as low incidence of severe side effects, support the continued use of LDR brachytherapy as a primary treatment modality for localized prostate cancer.
CRIS-Team Scopus Importer:2024-09-06
Keywords: I-125 seeds; LDR brachytherapy; low-intermediate-risk prostate cancer; low-risk prostate cancer; patient-reported outcomes; prostate cancer; toxicity; treatment outcomes

Principles of artificial intelligence in radiooncology - Huang, Yixing; Gomaa, Ahmed; Höfler, Daniel; Schubert, Philipp; Gaipl, Udo; Frey, Benjamin; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2024)
Keywords: Artificial intelligence; Radiation Oncology; Deep learning

Reirradiation for recurrent glioblastoma: the significance of the residual tumor volume - Mansoorian, Sina; Schmidt, Manuel; Weissmann, Thomas; Delev, Daniel; Heiland, Dieter Henrik; Coras, Roland; Stritzelberger, Jenny; Saake, Marc; Höfler, Daniel; Schubert, Philipp; Schmitter, Charlotte; Lettmaier, Sebastian; et al. (Journal of Neuro-Oncology, 2025)
Purpose: Recurrent glioblastoma has a poor prognosis, and its optimal management remains unclear. Reirradiation (re-RT) is a promising treatment option, but long-term outcomes and optimal patient selection criteria are not well established. Methods: This study analyzed 71 patients with recurrent CNS WHO grade 4, IDHwt glioblastoma (GBM) who underwent re-RT at the University of Erlangen-Nuremberg between January 2009 and June 2019. Imaging follow-ups were conducted every 3 months. Progression-free survival (PFS) was defined using RANO criteria. Outcomes, feasibility, and toxicity of re-RT were evaluated. Contrast-enhancing tumor volume was measured using a deep learning auto-segmentation pipeline with expert validation and jointly evaluated with clinical and molecular-pathologic factors. Results: Most patients were prescribed conventionally fractionated re-RT (84.5%) with 45 Gy in 1.8 Gy fractions, combined with temozolomide (TMZ, 49.3%) or lomustine (CCNU, 12.7%). Re-RT was completed as planned in 94.4% of patients. After a median follow-up of 73.8 months, 88.7% of patients had died. The median overall survival was 9.6 months, and the median progression-free survival was 5.3 months. Multivariate analysis identified residual contrast-enhancing tumor volume at re-RT (HR 1.040 per cm3, p < 0.001) as the single dominant predictor of overall survival. Conclusion: Conventional fractionated re-RT is a feasible and effective treatment for recurrent high-grade glioma. The significant prognostic impact of residual tumor volume highlights the importance of combining maximum-safe resection with re-RT for improved outcomes.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Chemoradiation; Glioblastoma; Prognostic factors; Radiotherapy; Recurrence; Reirradiation; Tumor volume

“sCT-Feasibility” - a feasibility study for deep learning-based MRI-only brain radiotherapy - Grigo, Johanna; Szkitsak, Juliane; Höfler, Daniel; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Radiation Oncology, 2024)
Background: Radiotherapy (RT) is an important treatment modality for patients with brain malignancies. Traditionally, computed tomography (CT) images are used for RT treatment planning whereas magnetic resonance imaging (MRI) images are used for tumor delineation. Therefore, MRI and CT need to be registered, which is an error prone process. The purpose of this clinical study is to investigate the clinical feasibility of a deep learning-based MRI-only workflow for brain radiotherapy, that eliminates the registration uncertainty through calculation of a synthetic CT (sCT) from MRI data. Methods: A total of 54 patients with an indication for radiation treatment of the brain and stereotactic mask immobilization will be recruited. All study patients will receive standard therapy and imaging including both CT and MRI. All patients will receive dedicated RT-MRI scans in treatment position. An sCT will be reconstructed from an acquired MRI DIXON-sequence using a commercially available deep learning solution on which subsequent radiotherapy planning will be performed. Through multiple quality assurance (QA) measures and reviews during the course of the study, the feasibility of an MRI-only workflow and comparative parameters between sCT and standard CT workflow will be investigated holistically. These QA measures include feasibility and quality of image guidance (IGRT) at the linear accelerator using sCT derived digitally reconstructed radiographs in addition to potential dosimetric deviations between the CT and sCT plan. The aim of this clinical study is to establish a brain MRI-only workflow as well as to identify risks and QA mechanisms to ensure a safe integration of deep learning-based sCT into radiotherapy planning and delivery. Discussion: Compared to CT, MRI offers a superior soft tissue contrast without additional radiation dose to the patients. However, up to now, even though the dosimetrical equivalence of CT and sCT has been shown in several retrospective studies, MRI-only workflows have still not been widely adopted. The present study aims to determine feasibility and safety of deep learning-based MRI-only radiotherapy in a holistic manner incorporating the whole radiotherapy workflow. Trial registration: NCT06106997.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Artificial intelligence; Deep learning; MRI; MRI-only workflow; MRonly; Radiotherapy; sCT; Stereotactic radiotherapy; Synthetic CT

The Segment Anything foundation model achieves favorable brain tumor auto-segmentation accuracy in MRI to support radiotherapy treatment planning - Putz, Florian; Beirami, Sogand; Schmidt, Manuel; May, Matthias; Grigo, Johanna; Weissmann, Thomas; Schubert, Philipp; Höfler, Daniel; Gomaa, Ahmed; Hassen, Ben Tkhayat; Lettmaier, Sebastian; Frey, Benjamin; et al. (Strahlentherapie und Onkologie, 2024)
Background: Promptable foundation auto-segmentation models like Segment Anything (SA, Meta AI, New York, USA) represent a novel class of universal deep learning auto-segmentation models that could be employed for interactive tumor auto-contouring in RT treatment planning. Methods: Segment Anything was evaluated in an interactive point-to-mask auto-segmentation task for glioma brain tumor auto-contouring in 16,744 transverse slices from 369 MRI datasets (BraTS 2020 dataset). Up to nine interactive point prompts were automatically placed per slice. Tumor boundaries were auto-segmented on contrast-enhanced T1w sequences. Out of the three auto-contours predicted by SA, accuracy was evaluated for the contour with the highest calculated IoU (Intersection over Union, “oracle mask,” simulating interactive model use with selection of the best tumor contour) and for the tumor contour with the highest model confidence (“suggested mask”). Results: Mean best IoU (mbIoU) using the best predicted tumor contour (oracle mask) in full MRI slices was 0.762 (IQR 0.713–0.917). The best 2D mask was achieved after a mean of 6.6 interactive point prompts (IQR 5–9). Segmentation accuracy was significantly better for high- compared to low-grade glioma cases (mbIoU 0.789 vs. 0.668). Accuracy was worse using the suggested mask (0.572). Stacking best tumor segmentations from transverse MRI slices, mean 3D Dice score for tumor auto-contouring was 0.872, which was improved to 0.919 by combining axial, sagittal, and coronal contours. Conclusion: The Segment Anything foundation segmentation model can achieve high accuracy for glioma brain tumor segmentation in MRI datasets. The results suggest that foundation segmentation models could facilitate RT treatment planning when properly integrated in a clinical application.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Artificial intelligence; Deep learning; Glioma; Interactive segmentation; Tumor auto-contouring

Treatment with (chemo)-radiation in old patients (≥76 years of age) with newly diagnosed non-metastatic squamous cell cancer of the head and neck region: real-world data from a tertiary referral center - Winkler, Leah-Sophie; Haderlein, Marlen; Semrau, Sabine; Putz, Florian; Höfler, Daniel; Müller, Sarina Katrin; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Schubert, Philipp (Frontiers in Oncology, 2024)
Purpose: Treatment of patients with cancer of the head and neck region is in focus in a multitude of studies. Of these patients, one patient group, those aged 76 and more, is mostly underrepresented despite requiring thorough and well-reasoned treatment decisions to offer curative treatment. This study investigates real-world data on curative treatment of old (≥76 years) patients with newly diagnosed squamous cell carcinoma of the head and neck region (HNSCC). Patients and methods: Between January 2010 and December 2021, we identified 71 patients older than 76 years with newly diagnosed HNSCC and cM0 at the Department of Radiation Oncology of the University Hospital of Erlangen-Nuremberg. Using electronic medical records, we analyzed treatment patterns and outcomes in terms of overall survival (OS), progression-free survival (PFS), and locoregional control (LRC) rate. Additionally, we performed univariate risk analysis and Cox regression in order to identify predictive factors associated with the abovementioned treatment outcomes. Results: The median follow-up was 18 months. OS was 83%, 79%, and 72% after 1 year, 2 years, and 3 years, respectively. PFS was 69%, 54%, and 46% after 1 year, 2 years, and 3 years, respectively. A total of 34 (48%) patients were treated with standard therapy according to current guidelines. The reasons for deviation from standard therapy before or during treatment were as follows: unfitness for cisplatin-based chemotherapy (n = 37), reduction of chemotherapy (n = 3), and dose reduction/interruption of radiotherapy (n = 8). Carboplatin-based systemic therapy showed improved PFS compared to cisplatin or cetuximab (60 vs. 28 vs. 15 months, p = 0.037) but without impact on OS (83 vs. 52 vs. 38 months, p = 0.807). Oropharyngeal tumor localization (p = 0.026) and combined treatment (surgery and postoperative treatment) (p = 0.008) were significant predictors for a better OS. In multivariate analysis, oropharyngeal tumor localization (p = 0.011) and combined treatment (p = 0.041) showed significantly increased PFS. After 1 year, 2 years, and 3 years, the cumulative incidence of locoregional recurrences (LRRs) was 13%, 24%, and 27%, respectively, and was significantly decreased in patients with oropharyngeal tumor localization (p = 0.037). Conclusions: Adherence to treatment protocols for radiotherapy alone in old patients with HNSCC is good, whereas the application of concurrent chemotherapy often deviates from guidelines in terms of de-escalation. An important risk factor for decreased OS, PFS, and a higher rate of LRR appears to be non-oropharyngeal tumor location in old patients.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemoradiation; head and neck cancer; old patients; squamous cell carcinoma; tumor localization

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02